1974
DOI: 10.1128/aac.5.2.153
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Herpesvirus Action of Isoprinosine

Abstract: Anti-herpesvirus effects of Isoprinosine were found to be condition-dependent in vitro and in vivo. A herpes type 1 strain, grown in primary rabbit kidney cells, was not susceptible to Isoprinosine when cytopathic effect was evaluated, but was modestly inhibited when plaque-forming methocel overlay was used in the same cell line. However, the growth of a herpes type 2 strain was inhibited by Isoprinosine in this system when cytopathic effect was evaluated. Both viruses produced an encephalitis in hamsters afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1977
1977
1988
1988

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Inosiplex is also a virustatic agent which has demonstrated efficacy against different viruses [2,4,19,271. Inosiplex is believed to exert an inhibitory action on the process of viral replication in host cells as well as augmenting effector cell immune responses [2, 4 , 7, 8, 19-22, 27, 301.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inosiplex is also a virustatic agent which has demonstrated efficacy against different viruses [2,4,19,271. Inosiplex is believed to exert an inhibitory action on the process of viral replication in host cells as well as augmenting effector cell immune responses [2, 4 , 7, 8, 19-22, 27, 301.…”
Section: Resultsmentioning
confidence: 99%
“…However, direct antiviral agents and actions that alter host immunity are reported to have varying effects on the course of the disease [3, 4, 12, 14, 15, 18, 25, 26, 281. I t has been proposed that inosiplex may have an influence on viral diseases because of its direct antiviral and immunomodulatory properties [2,4,7,[19][20][21][22]27, 301. Huttenlocher and Mattson [12] and Streletz and Cracco [28] reported that inosiplex was beneficial in reducing the morbidity and mortality associated with SSPE.…”
mentioning
confidence: 99%
“…Effects on RNA metabolism have been demonstrated [18] (Hadden unpublished). Based upon similarities to interferon action, later changes are suspected and experiments are in progress to determine if this is the case.…”
Section: Mechanisms Of Action Of Immunotherapeutic Agentsmentioning
confidence: 99%
“…Of the chemical agents, levamisole's proproliferative actions on lymphocytes have been parallelled to imidazole and the actions of both have been linked to decreases in cyclic AMP levels and increases in cyclic GMP levels [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Effects of levamisole on monocyte and neutrophil cyclic GMP levels correlate with effects on chemotaxis, phagocytosis, and bactericidal capacity [2,37].…”
Section: Mechanisms Of Action Of Immunotherapeutic Agentsmentioning
confidence: 99%
“…Based on results obtained with in vitro systems (12), laboratory animals (9,11), and human volunteers (4), the drug's mechanism of action appears to involve a stimulation of the cellular immune system, in particular the "activated lymphocytes" that have been previously sensitized to foreign viral protein. Evidence that impaired cellular immunity can prevent or delay recovery from viral infections has come from studies by Blanden in an animal model (1)(2)(3) and in patients with congenital abnormalities of the immune system (6,10).…”
mentioning
confidence: 99%